A study on the factors that affecting gross domestic products in Malaysia / Nurul Alia Izzati Abd Jalil - Abd Jalil, Nurul Alia Izzati (2017)
The changes in gross domestic product in Malaysia have attracted the attention and believe to be the most studied construct in finance. Gross domestic product is one of the indicators of the economy stability. Therefore, this study is to determine the factors that affect gross domestic products in Malaysia. The objectives of this study are to measure the factors that affect gross domestic product in Malaysia and to identify the most affected factor between the factors listed.